Navigating Inclusion: Challenges Faced by Teachers in the Peninsula of Santa Elena in Supporting Students and Families with Special Education Needs - Gándara Vivar , María Gabriela; Inzhivotkina, Yana (Arandu UTIC, 2024)
This paper examines the evolving landscape of inclusive education in Ecuador, focusing on the challenges faced by special education (SEN) teachers, especially in the Santa Elena region. Ecuador’s Ministry of Education has adopted inclusive education policies to support students with various physical, cognitive, and socioemotional needs. However, SEN teachers encounter substantial challenges, such as managing classrooms with diverse disabilities, limited institutional support, non-instructional responsibilities, and lack of public recognition. These obstacles contribute to high stress and burnout rates, with many SEN teachers leaving the profession within a decade, leading to a shortage of qualified professionals and diminished quality of SEN programs. The study used a quantitative approach, surveying 11 SEN teachers to identify the primary challenges they face. Key findings highlight widespread misconceptions about SEN teaching, insufficient support from parents and colleagues, and the difficulty of balancing instructional and non-instructional tasks. Teachers reported difficulties handling multiple disabilities and maintaining inclusive environments, often without adequate resources or professional development. This initial analysis emphasizes the need for targeted support systems, including specialized resources and structured professional development, to alleviate the burdens on SEN teachers. By addressing these challenges, policymakers can enhance educational inclusivity and improve the learning environment for students with special needs. This study serves as a foundation for further research and policy recommendations aimed at fostering a more supportive, inclusive community in Santa Elena.